Modification method for improving oxygen catalytic performance of transition metal-based compound through trace iron modification

By modifying trace iron on transition metal-based compounds and using cyclic voltammetry and constant current electrodeposition methods, the problem of instability in the electrocatalytic process of transition metal-based compounds is solved, which significantly improves its catalytic performance and stability in zinc-air batteries.

CN119819318APending Publication Date: 2025-04-15广州云皓科技技术有限公司
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510032707.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-09
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

Transition metal-based compounds have problems such as unstable activity, poor conductivity and low reaction efficiency during electrocatalysis, which limits their application in electrochemical energy storage devices such as zinc air batteries.

Method used

Cyclic voltammetry electrodeposition method and constant current deposition method are used to uniformly deposit trace amounts of iron on the substrate of transition metal-based compound. By optimizing the iron modification amount and preparation process, the iron modification amount is accurately controlled and the exposure of the electronic structure and active sites on the surface of the catalyst is improved.

Benefits of technology

The catalytic performance of oxygen reduction reaction (ORR) and oxygen precipitation reaction (OER) is significantly enhanced, the stability and applicability of the catalyst are improved, and it is suitable for electrochemical energy storage devices such as zinc air batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119819318A_ABST
    Figure CN119819318A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of catalytic materials, and particularly relates to a modification method for improving the oxygen catalytic performance of a transition metal-based compound through trace iron modification. By adopting electrodeposition means such as cyclic voltammetry and constant current method, the surface reconstruction behavior of the transition metal-based oxide is optimized by accurately controlling the modification amount of iron and the uniform distribution of trace iron, so that the catalytic activity and stability of the transition metal-based oxide in electrochemical reaction are improved; therefore, the material is suitable for electrochemical energy storage devices such as rechargeable zinc-air batteries and the like. Meanwhile, the modification method has the main characteristics of low cost, high stability and high activity, and the material activity and stability of the transition metal-based compound electrode are remarkably improved by accurately controlling the iron modification amount and optimizing the structure.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalytic materials, and in particular relates to a modification method for improving the oxygen catalytic performance of transition metal-based compounds by modifying them with trace amounts of iron. Background Art

[0002] With the rapid development of industrialization and the growing global energy demand, the development of efficient, stable and low-cost electrocatalysts has become the key to solving the problem of energy storage and conversion. For example, zinc-air batteries, as an energy storage device with high energy density, low cost and environmental protection advantages, have received widespread attention in recent years. However, the kinetic efficiency of zinc-air batteries in oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) still needs to be improved to achieve wider application.

[0003] Transition metals, such as manganese (Mn), iron (Fe), nickel (Ni), and cobalt (Co), are considered potential oxygen catalysts due to their abundant reserves, environmental friendliness, good stability, and strong adjustability. However, transition metal-based compounds often exhibit problems such as unstable activity, poor conductivity, and low reaction efficiency during electrocatalysis, which restricts their application in electrochemical energy storage devices such as zinc-air batteries. At present, transition metal-based materials such as Mn, Fe, Ni, and Co have shown great application potential as substitutes for precious metal and rare metal-based materials. However, the poor redox kinetics of transition metal-based compounds limit the performance of zinc-air batteries. In particular, transition metal oxides, due to their inherent low conductivity, hinder electron transfer during oxygen catalysis.

[0004] In order to overcome these defects, researchers have tried to modify transition metal-based compounds by introducing other elements. Among them, the Fe element is considered to be an effective oxygen catalytic material regulating element due to its low cost, environmental friendliness, unique electronic structure and high oxygen catalytic activity. Currently reported modification methods, for example, Chinese invention patent CN113383115B provides an electrolyte for electrodeposition of an alloy of a first metal and a second metal, wherein the first metal is selected from cobalt, copper and a mixture thereof, and the second metal is selected from manganese, zinc and a mixture thereof, and is mainly used to manufacture electrical cobalt interconnects or copper interconnects in integrated circuits. However, it does not involve electrochemical catalytic applications, and the preparation process and performance stability of the alloy need to be further verified. Chinese invention patent CN110071299A provides a nickel-iron alloy / nitrogen-doped carbon (Ni x Fe y / NC) electrocatalyst preparation method and application in rechargeable zinc-air battery, the combination of nickel-iron alloy and nitrogen-doped carbon makes it have good ORR and OER performance at the same time, and can provide good catalytic performance during charging and discharging. However, the preparation of the catalyst involves multiple complex chemical reactions and high-temperature annealing processes. Although the performance is excellent, the process is complicated and the energy consumption is high. At the same time, since the distribution of doping elements is difficult to accurately control, excessive doping may lead to instability of the material structure, thereby affecting its long-term catalytic performance. Chinese invention patent CN118600507A provides a manufacturing process for low surface energy electrodes, which adopts low surface energy modification technology. By introducing a super-hydrophobic PTFE material on the electrode surface, the surface energy of the electrode is reduced, and it is mainly used to improve the efficiency of water electrolysis hydrogen production. Although surface modification can effectively reduce the surface energy, it has limited effect on improving the conductivity and oxygen catalytic reaction performance of the overall electrode. It is mainly suitable for the field of hydrogen production, but cannot meet the needs of oxygen reduction and oxygen evolution reaction. Chinese invention patent CN116971000A provides an electroplating process for preparing permanent magnetic FePt thick film by step-by-step electrodeposition, which controls the thickness of the permanent magnetic film by adjusting the number and time of step-by-step deposition, and promotes the formation of the permanent magnetic phase of the film by pretreatment. However, the preparation of permanent magnetic FePt thick film by step-by-step electrodeposition focuses on improving the permanent magnetic properties, which has no direct correlation with the improvement of electrochemical catalytic performance.

[0005] In summary, although appropriate iron doping can improve the oxygen catalytic performance of transition metal-based compounds, it has not yet been widely used due to the difficulty in controlling the doping amount and the new problems that may be introduced during the doping process, such as decreased material stability. Therefore, it is particularly important to develop a method that can accurately control the amount of iron modification and improve the performance of transition metal-based compound oxygen catalysts. Summary of the invention

[0006] In order to overcome the shortcomings of the above-mentioned prior art, the present invention provides a modification method for improving the oxygen catalytic performance of transition metal-based compounds by modifying them with trace amounts of iron. The method adopts cyclic voltammetry electrodeposition and constant current deposition to uniformly deposit trace amounts of iron on a transition metal-based compound substrate, and optimizes the iron modification amount and the preparation process to accurately control the iron modification amount, so that the modified transition metal-based compound exhibits excellent catalytic performance in OER and ORR, making it suitable for electrochemical energy storage devices such as zinc-air batteries.

[0007] In order to achieve the above object, the technical solution adopted by the present invention is:

[0008] The first aspect of the present invention provides a method for modifying a transition metal-based compound by modifying it with trace amounts of iron to improve its oxygen catalytic performance, the method comprising the following steps:

[0009] S1. dissolving a transition metal-based compound salt and a conductive agent in water to prepare an electrodeposition solution;

[0010] S2, adding iron salt and conductive agent into water to prepare electrodeposition modification solution;

[0011] S3, using the conductive substrate as the working electrode, placing the conductive substrate in the electrodeposition solution of S1, and then performing electrodeposition by cyclic voltammetry or constant current method to prepare a transition metal-based compound / conductive substrate electrode material;

[0012] S4. Using the transition metal-based compound / conductive substrate electrode material of S3 as the working electrode, a constant current method is used to deposit an iron modification layer on the electrode surface, and then heat treatment is performed to obtain an iron-modified transition metal-based compound oxygen catalytic material.

[0013] The present invention uses a cleverly designed iron modification strategy to apply this method for the first time to improve the oxygen catalytic performance of transition metal-based compounds. By precisely controlling the amount and distribution of iron modification, the exposure of the electronic structure and active sites on the catalyst surface is improved, thereby significantly enhancing the catalytic performance of oxygen reduction reaction (ORR) and oxygen evolution reaction (OER). This innovative trace iron modification method is a brand-new application in the field of electrocatalysis, with clear technical breakthroughs and application value.

[0014] Preferably, in the electrodeposition solution of S1, the concentration of the transition metal-based precursor is 0.001 to 5 mol / L, and the molar ratio of the transition metal-based precursor to the conductive agent is 1:100 to 100:1. By optimizing the formula of the electrodeposition solution (the molar ratio of the transition metal-based precursor to the conductive agent), the best transition metal-based precursor / conductive substrate deposition effect can be obtained.

[0015] Preferably, in the electrodeposition modification solution of S2, the concentration of iron ions is 0.001 to 2 mol / L, and the molar ratio of iron ions to the conductive agent is 1:100 to 100:1. By adjusting the molar ratio of the iron ion concentration to the conductive agent, trace control of the iron element is achieved.

[0016] Preferably, in S3, the potential scanning interval of the cyclic voltammetry is 0V to -2V, the scanning rate is 0.01 to 500mV / s, and the number of cycles is 2 to 5000 times; the current of the constant current method is -0.001 to -1000mA / cm 2 , the deposition time is 1 to 3600 min.

[0017] Preferably, in S4, a three-electrode system (including a working electrode, a reference electrode and a counter electrode) and cyclic voltammetry or constant current method are used to deposit an iron modification layer on the electrode surface, wherein the potential scanning interval of the cyclic voltammetry method is 0V to -2V, the scanning rate is 0.01 to 500mV / s, and the number of cycles is 2 to 5000 times; the current of the constant current method is -0.001 to -500mA / cm 2 , the deposition time is 1 to 3600 min. By adjusting the deposition time, voltage or current range, uniform deposition of the iron modification layer can be achieved.

[0018] Preferably, in S4, the temperature of the heat treatment is 20-100° C., and the treatment time is less than 10 hours. The heat treatment can promote the deep integration of the iron element and the matrix material, and further optimize the electronic structure.

[0019] Preferably, in S1 or S2, the conductive agent includes ionic compounds such as ammonium sulfate, boric acid, potassium dihydrogen phosphate, etc. for adjusting the acidity and alkalinity of the deposition liquid, and ionic compounds such as sodium chloride, potassium chloride, etc. for increasing the conductivity of the deposition liquid.

[0020] Preferably, in S1, the transition metal-based precursor is a transition metal compound such as a transition metal ion salt or an oxide, which can be dissolved in water to provide metal ions; in S2, the iron salt includes iron-containing compounds such as ferric chloride, ferric sulfate, ferric nitrate, and ferric acetate, which can be dissolved in water to provide divalent or trivalent iron ions; in S3, the conductive substrate is a metal electrode substrate material or a non-metallic electrode substrate material, including metal electrode substrate materials such as gold, silver, nickel, iron, and copper, or non-metallic electrode substrate materials such as conductive glass, carbon cloth, and glassy carbon.

[0021] Preferably, the conductive substrate is pre-treated by cleaning and surface activation before use to improve its surface cleanliness and electrochemical activity.

[0022] The second aspect of the present invention provides a transition metal-based compound oxygen catalytic material prepared by the modification method described in the first aspect.

[0023] The third aspect of the present invention provides the use of the transition metal-based compound oxygen catalytic material described in the second aspect in the preparation of an electrochemical energy storage device, wherein the electrochemical energy storage device includes a zinc, iron, lithium, or aluminum metal air battery.

[0024] The method of the present invention optimizes the surface reconstruction behavior of transition metal-based oxides by uniformly distributing trace amounts of iron, thereby improving the oxygen catalytic activity and stability of the oxides in electrochemical reactions, making them suitable for electrochemical energy storage devices such as rechargeable metal-air batteries.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] The present invention discloses a modification method for improving the oxygen catalytic performance of transition metal-based compounds by modifying them with trace amounts of iron. The method uses electrodeposition methods such as cyclic voltammetry and constant current method to optimize the surface reconstruction behavior of transition metal-based oxides by precisely controlling the amount of iron modification and the uniform distribution of trace amounts of iron, thereby improving the catalytic activity and stability in electrochemical reactions, making them suitable for electrochemical energy storage devices such as rechargeable metal-air batteries. At the same time, the modification method is mainly characterized by low cost, high stability and high activity. By precisely controlling the amount of iron modification and optimizing the structure, the material activity and stability of transition metal-based compound electrodes are significantly improved. Specifically, the present invention has the following advantages:

[0027] (1) Precise modification control: By optimizing the electrodeposition parameters, the uniform distribution of the iron modification layer is achieved, overcoming the problems of material unevenness and difficult control of doping amount in traditional doping processes.

[0028] (2) Significant performance improvement: The modified catalysts exhibit lower overpotential, higher current density and better stability in both ORR and OER reactions.

[0029] (3) Strong applicability: The method is simple and easy to operate, and can be easily prepared in batches at low cost, making it suitable for large-scale application in various electrochemical energy storage devices such as metal-air batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 The SEM image of Fe / MnO2 / NF prepared in Example 1;

[0031] Figure 2 Elemental energy spectrum of Fe / MnO2 / NF prepared in Example 1;

[0032] Figure 3 This is the SEM image of Fe / CoSe / NF prepared in Example 2;

[0033] Figure 4 Elemental energy spectrum of Fe / CoSe / NF prepared in Example 2;

[0034] Figure 5 Electrochemical performance of the Fe / MnO2 / NF electrode prepared in Example 1, the MnO2 / NF electrode prepared in Comparative Example 1, and the nickel foam (NF) substrate in oxygen evolution reaction (OER);

[0035] Figure 6 Electrochemical performance of the Fe / CoSe / NF electrode prepared in Example 2, the CoSe / NF electrode prepared in Comparative Example 2, and the nickel foam (NF) substrate in the OER reaction;

[0036] Figure 7Linear sweep voltammetry (LSV) curves of the Fe / MnO2 / NF electrocatalyst prepared in Example 1, the MnO2 / NF electrocatalyst prepared in Comparative Example 1, and the commercial Pt / C catalyst in 0.1M KOH solution at 1600rpm;

[0037] Figure 8 Linear sweep voltammetry (LSV) curves of the Fe / CoSe / NF electrocatalyst prepared in Example 2, the CoSe / NF electrocatalyst prepared in Comparative Example 2, and the commercial Pt / C catalyst in 0.1M KOH solution at 1600rpm;

[0038] Fig. 9 The test results of the open circuit voltage (OCV) of the zinc-air battery assembled with the Fe / MnO2 / NF electrode prepared in Example 1;

[0039] Fig.10 The test results of the open circuit voltage (OCV) of the zinc-air battery assembled with the Fe / CoSe / NF electrode prepared in Example 2;

[0040] Fig.11 This is a stability test curve of the Fe / MnO2 / NF prepared in Example 1 as a cathode electrode of a zinc-air battery;

[0041] Fig.12 This is the stability test curve of the Fe / CoSe / NF prepared in Example 2 as the cathode electrode of the zinc-air battery. DETAILED DESCRIPTION

[0042] The specific embodiments of the present invention are further described below. It should be noted that the description of these embodiments is used to help understand the present invention, but does not constitute a limitation of the present invention. In addition, the technical features involved in each embodiment of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0043] The experimental methods in the following examples are conventional methods unless otherwise specified, and the experimental materials used in the following examples are commercially available unless otherwise specified.

[0044] In the following embodiments, the substrate is pretreated before use: a nickel foam (NF) with a size of 1cm×2cm×0.3mm is used as the substrate, and pretreatments such as cleaning and surface activation are performed. The cleaning step includes ultrasonic cleaning using acetone, an acid solution of a suitable concentration, deionized water and anhydrous ethanol to remove surface impurities. First, the nickel foam is treated with acetone to remove the oil stains on the surface, and then the nickel foam is treated with dilute acid to remove the oxide layer on the surface. The dilute acid described here is dilute hydrochloric acid or dilute sulfuric acid with a concentration of 0.5 to 2 mol / L. Finally, anhydrous ethanol and deionized water are used to clean the nickel foam. The treatment process is carried out in an ultrasonic cleaning machine, and each process lasts for 1 to 20 minutes. Then it is placed in a vacuum drying oven and dried at 60°C for 40 minutes.

[0045] Embodiment 1:

[0046] (1) The pretreated nickel foam was sandwiched on a working electrode platinum sheet and immersed in a 1 cm×1 cm area in a solution containing 0.5 mol / L manganese sulfate (MnSO4·H2O) and 0.1 mol / L ammonium sulfate ((NH4)2SO4), the auxiliary electrode was a carbon rod, and the reference electrode was a saturated calomel electrode. Cyclic voltammetry was used to perform electrodeposition for 10 cycles in a voltage window of -0.8 to -1.5 V and a scan rate of 5 mV / s. After the electrodeposition was completed, the electrode was washed with deionized water and dried at room temperature to obtain a MnO2 / NF electrode;

[0047] (2) The MnO2 / NF electrode was immersed in a modification solution consisting of 0.01 mol / L ferric chloride (FeCl3) and 0.01 mol / L potassium chloride (KCl) with an area of ​​1 cm×1 cm. The auxiliary electrode was a carbon rod and the reference electrode was a saturated calomel electrode. The iron modification layer was deposited on the electrode surface by constant current method. The current of the constant current method was set to -3 mA / cm 2 The deposition time was 5 min. After the electrodeposition was completed, it was placed in an oven for heat treatment at 60 °C for 20 min to obtain the Fe / MnO2 / NF electrocatalyst.

[0048] Embodiment 2:

[0049] (1) The pretreated nickel foam was sandwiched on the working electrode platinum sheet and immersed in an area of ​​1 cm × 1 cm in a solution containing 0.2 mol / L dicobalt chloride hexahydrate (CoCl2·6H2O), 0.1 mol / L selenium dioxide (SeO2) and 0.1 mol / L ammonium sulfate ((NH4)2SO4). The auxiliary electrode was a carbon rod and the reference electrode was a saturated calomel electrode. The constant current method was used at -10 mA / cm 2 The current electrodeposition was performed under current for 20 min, and after the electrodeposition was completed, the electrode was washed with deionized water and dried at room temperature to obtain a CoSe / NF electrode;

[0050] (2) The CoSe / NF electrode was immersed in a modification solution consisting of 0.01 mol / L ferric chloride (FeCl3) and 0.01 mol / L potassium chloride (KCl) with an area of ​​1 cm×1 cm. The auxiliary electrode was a carbon rod and the reference electrode was a saturated calomel electrode. The iron modification layer was deposited on the electrode surface by constant current method. The current of the constant current method was set to -3 mA / cm 2 The deposition time was 1 min. After the electrodeposition was completed, it was placed in an oven for heat treatment at 60°C for 20 min to obtain the Fe / CoSe / NF electrocatalyst.

[0051] Comparative Example 1:

[0052] The pretreated nickel foam was sandwiched on the working electrode platinum sheet and immersed in an area of ​​1 cm×1 cm in a solution containing 0.5 mol / L manganese sulfate (MnSO4) and 0.1 mol / L ammonium sulfate ((NH4)2SO4). The auxiliary electrode was a carbon rod and the reference electrode was a saturated calomel electrode. Cyclic voltammetry was used to perform electrodeposition for 10 cycles in a voltage window of -0.8 to -1.5 V and a scan rate of 5 mV / s. After the electrodeposition was completed, it was washed with deionized water and dried at room temperature to obtain a MnO2 / NF electrode.

[0053] Comparative Example 2:

[0054] The pretreated nickel foam was sandwiched on the working electrode platinum sheet and immersed in an area of ​​1 cm × 1 cm in a solution containing 0.2 mol / L dicobalt chloride hexahydrate (CoCl2·6H2O), 0.1 mol / L selenium dioxide (SeO2) and 0.1 mol / L ammonium sulfate ((NH4)2SO4). The auxiliary electrode was a carbon rod and the reference electrode was a saturated calomel electrode. The constant current method was used at -10 mA / cm 2 The electrodeposition was carried out under electric current for 20 min. After the electrodeposition was completed, it was washed with deionized water and dried at room temperature to obtain a CoSe / NF electrode.

[0055] Experimental Example 1: Material Characterization

[0056] The structure, morphology and chemical composition of the Fe-modified transition metal-based compound electrodes modified in Examples 1 and 2 were characterized in detail using modern analytical techniques such as scanning electron microscopy (SEM) and transmission electron microscopy (TEM).

[0057] Figure 1 The scanning electron microscope image (SEM) shows the nanosheet structure of the electrocatalyst prepared in Example 1. The iron-modified MnO2 deposited on the surface of the nickel foam is composed of wrinkled nanosheets, and the nanosheet-like iron-modified MnO2 is accumulated on the surface of the nickel foam into a three-dimensional nanoporous structure. Figure 2The element spectrum shows the uniform distribution of Fe and Mn elements on the surface of the material.

[0058] Figure 3 The scanning electron microscope image (SEM) shows the nanoparticle structure of the electrocatalyst prepared in Example 2. The iron-modified CoSe deposited on the surface of the nickel foam is composed of wrinkled nanoparticles. The iron-modified CoSe nanoparticles are tightly stacked on the surface of the substrate to construct a catalyst with a three-dimensional stable structure. Figure 4 The element energy spectrum shows that Fe, Co and Se elements are evenly distributed on the surface of the material.

[0059] Experimental Example 2: Electrochemical Testing of Materials

[0060] The electrocatalysts obtained in Examples 1 and 2 and Comparative Examples 1 and 2 were tested using a three-electrode system. The test conditions were normal pressure and room temperature, the electrodeposition solution was 1 M KOH, the reference electrode was a Hg / HgO electrode, the counter electrode was a graphite rod, the working electrode was the electrocatalysts obtained in Examples 1 and 2 and Comparative Examples 1 and 2, and the infiltration area was 1×0.5 cm 2 The scan rate of the polarization curve was 5 mV / s, and the OER potential scan range was 1.0-1.8 V (vs. RHE). All tests were started after 10 cyclic voltammetry stabilizations, and the data were corrected by iR compensation.

[0061] Figure 5 The electrochemical performance of the Fe / MnO2 / NF electrode prepared in Example 1, the MnO2 / NF electrode prepared in Comparative Example 1, and the nickel foam (NF) substrate in oxygen evolution reaction (OER) is shown. It can be seen that the Fe / MnO2 / NF electrode has a good electrochemical performance at a current density of 10 mA cm -2 The overpotential is 263mV at 300mA·cm -2 The value is 323.34 mV, which is significantly better than that of the comparative MnO2 / NF electrode (363 mV, 10 mA cm -2 ) and nickel foam electrodes. In addition, the catalytic performance of Fe / MnO2 / NF was significantly higher than that of the benchmark noble metal catalyst RuO2 (10 mA cm -2 The above results demonstrate the effectiveness of the iron modification method in improving the catalytic activity of oxygen evolution. Iron modification enhances the interaction between the catalyst and the electrolyte interface, thereby reducing the reaction overpotential.

[0062] Figure 6 The electrochemical performance of the Fe / CoSe / NF electrode prepared in Example 2, the CoSe / NF electrode prepared in Comparative Example 2, and the nickel foam substrate in the OER reaction is compared. The results show that the Fe / CoSe / NF electrode has a high electrochemical performance at 10 mA cm -2The overpotential at 300 mA·cm is 83 mV. -2 In contrast, the overpotentials of CoSe / NF in Comparative Example 2 at the same current density were 93 mV and 384 mV, respectively, proving that Fe modification has a significant effect on improving the catalytic activity of CoSe electrode at high current density.

[0063] Figure 7 The linear sweep voltammetry (LSV) curves of the Fe / MnO2 / NF electrocatalyst prepared in Example 1, the MnO2 / NF electrocatalyst prepared in Comparative Example 1, and the commercial Pt / C catalyst in 0.1M KOH solution at 1600rpm are shown. The results show that the half-wave potential of the Fe / MnO2 / NF catalyst is 0.7733V, which is higher than the 0.6133V of the MnO2 / NF catalyst and close to the 0.8533V of Pt / C. At the same time, its limiting current density reaches 4.62mA·cm -2 , compared with 5.08 mA cm for Pt / C -2 This indicates that the iron-modified MnO2 electrode prepared by this method has excellent oxygen reduction reaction (ORR) catalytic performance and is suitable for zinc-air battery applications.

[0064] Figure 8 The linear sweep voltammetry (LSV) curves of the Fe / CoSe / NF electrocatalyst prepared in Example 2, the CoSe / NF electrocatalyst prepared in Comparative Example 2, and the commercial Pt / C catalyst in 0.1M KOH solution at 1600rpm are shown. The results show that the half-wave potential of the Fe / CoSe / NF catalyst is 0.7733V, which is higher than the 0.6133V of the CoSe / NF catalyst and close to the 0.8533V of Pt / C. At the same time, its limiting current density reaches 4.62mA·cm -2 , compared with 5.08 mA cm for Pt / C -2 This indicates that the iron-modified MnO2 electrode prepared by this method has excellent oxygen reduction reaction (ORR) catalytic performance and is suitable for zinc-air battery applications.

[0065] Experimental Example 3: Zinc-air battery test

[0066] A typical zinc-air battery consists of three parts: an anode, an electrolyte, and a cathode. The anode is made of a zinc foil with a thickness of 0.2 mm, which must be polished to remove zinc oxide on the surface before use; a 6.0M KOH and 0.2M Zn(Ac)2 solution is prepared as the electrolyte; the air cathode consists of a catalyst layer and a waterproof and breathable layer, the catalyst layer is the electrocatalyst material of Examples 1, 2 and Comparative Examples 1, 2, the waterproof and breathable layer is a waterproof and breathable membrane, and a mixed material electrocatalyst prepared by mixing Pt / C and RuO2 in a mass ratio of 1:1 is used as a comparative sample, and a Pt / C+RuO2 catalyst with the same loading as the Fe / MnO2 / NF electrocatalyst is dripped onto the pretreated nickel foam as a catalyst layer.

[0067] Fig. 9 The test results of the open circuit voltage (OCV) of the zinc-air battery assembled with the Fe / MnO2 / NF electrode prepared in Example 1 are shown. The results show that the OCV of the zinc-air battery with the Fe / MnO2 / NF electrode is 1.422V, which is better than that of the MnO2 / NF electrode in Comparative Example 1. 2 / NF electrode (1.321 V), indicating the effectiveness of the Fe / MnO2 / NF catalyst of the present invention in improving the initial performance of zinc-air batteries.

[0068] Fig.10 The test results of the open circuit voltage (OCV) of the zinc-air battery assembled with the Fe / CoSe / NF electrode prepared in Example 2 are shown. The results show that the OCV of the zinc-air battery with the Fe / CoSe / NF electrode is 1.321V, which is better than the CoSe / NF electrode (1.103V) ​​of Comparative Example 1, indicating the effectiveness of the Fe / CoSe / NF catalyst of the present invention in improving the initial performance of the zinc-air battery.

[0069] In addition, the Fe / MnO2 / NF of Example 1, the Fe / CoSe / NF of Example 2, and the commercial noble metal RuO2+Pt / C mixed material electrocatalyst were assembled into zinc-air batteries, and then the batteries were charged at a current density of 5 mA cm -2 The constant current charge and discharge test was carried out under the condition of 10 minutes of discharge and 10 minutes of charge as one cycle.

[0070] Fig.11 The stability test curve of Fe / MnO2 / NF prepared in Example 1 as the cathode electrode of zinc-air battery is shown. The results show that at 5 mA·cm -2 At the current density, the Fe / MnO2 / NF electrode maintained a stable charge and discharge voltage for 1000 hours, while the RuO2+Pt / C cathode only maintained it for 700 hours under the same conditions, indicating that the Fe / MnO2 / NF electrode has significant long-term cycle stability.

[0071] Fig.12 The stability test curve of Fe / CoSe / NF prepared in Example 2 as the cathode electrode of zinc-air battery is shown. The results show that at 5 mA·cm -2 At the current density, the Fe / CoSe / NF electrode maintains a stable charge and discharge voltage for 1200 h, indicating that the Fe / CoSe / NF electrode has remarkable long-term cycling stability.

[0072] In summary, the present invention significantly improves the catalytic activity and stability of the material in oxygen reduction (ORR) and oxygen evolution (OER) reactions by modifying the transition metal-based oxide catalyst with a trace amount of iron, making it particularly suitable for electrochemical energy storage devices such as rechargeable metal-air batteries. At the same time, the Fe-modified transition metal-based catalyst prepared by the method of the present invention exhibits lower overpotential and better charge and discharge stability at high current density, and is superior to the current mainstream precious metal catalysts. Therefore, the modification method of the present invention has broad application prospects, especially in the field of low-cost and high-performance electrochemical energy storage devices, and is expected to replace part of the precious metal-based materials, providing practical and effective technical support for the development of rechargeable metal-air batteries.

[0073] The embodiments of the present invention are described in detail above, but the present invention is not limited to the described embodiments. For those skilled in the art, various changes, modifications, substitutions and variations of these embodiments are made without departing from the principles and spirit of the present invention, and still fall within the protection scope of the present invention.

Claims

1. A method for improving the oxygen catalytic performance of transition metal-based compounds by modifying them with trace amounts of iron, characterized in that: The following steps are involved: S1, dissolving a transition metal-based precursor and a conductive agent in water to prepare an electrodeposition solution; S2, adding iron salt and conductive agent into water to prepare electrodeposition modification solution; S3, using the conductive substrate as the working electrode, placing the conductive substrate in the electrodeposition solution of S1, and then performing electrodeposition by cyclic voltammetry or constant current method to prepare a transition metal-based compound / conductive substrate electrode material; S4. Using the transition metal-based compound / base electrode material of S3 as the working electrode, a modified iron layer is deposited on the electrode surface by cyclic voltammetry or constant current method, and then heat treatment is performed to obtain an iron-modified transition metal-based compound oxygen catalytic material.

2. According to claim 1, a method for improving the oxygen catalytic performance of transition metal-based compounds by modifying with trace iron, characterized in that: In the electrodeposition solution of S1, the concentration of the transition metal-based precursor is 0.001 to 5 mol / L, and the molar ratio of the transition metal-based precursor to the conductive agent is 1:100 to 100:

1.

3. According to claim 1, a method for improving the oxygen catalytic performance of transition metal-based compounds by modifying with trace amounts of iron, characterized in that: In the electrodeposition modification solution of S2, the concentration of iron ions is 0.001 to 2 mol / L, and the molar ratio of iron ions to the conductive agent is 1:100 to 100:

1.

4. According to claim 1, a method for improving the oxygen catalytic performance of transition metal-based compounds by modifying with trace iron, characterized in that: In S3, the potential scanning range of cyclic voltammetry is 0V~-2V, the scanning rate is 0.01~500mV / s, and the number of cycles is 2~5000 times; the current of constant current method is -0.001~-1000mA / cm 2 , the deposition time is 1 to 3600 min.

5. The modification method for improving the oxygen catalytic performance of transition metal-based compounds by modifying with trace amounts of iron according to claim 1, characterized in that: In S4, the potential scanning range of cyclic voltammetry is 0V~-2V, the scanning rate is 0.01~500mV / s, and the number of cycles is 2~5000 times; the current of constant current method is -0.001~-500mA / cm 2 , the deposition time is 1 to 3600 min.

6. The method for improving the oxygen catalytic performance of transition metal-based compounds by modifying with trace amounts of iron according to claim 1, characterized in that: In S4, the heat treatment temperature is 20 to 100° C., and the treatment time is less than 10 hours.

7. The method for improving the oxygen catalytic performance of transition metal-based compounds by modifying with trace amounts of iron according to claim 1, characterized in that: In S1 or S2, the conductive agent is an ionic compound used to adjust the acidity or alkalinity of the deposition liquid or to increase the conductivity of the deposition liquid, including ammonium sulfate, boric acid, potassium dihydrogen phosphate, sodium chloride, and potassium chloride.

8. The method for improving the oxygen catalytic performance of transition metal-based compounds by modifying with trace amounts of iron according to claim 1, characterized in that: In S1, the transition metal-based precursor is a transition metal compound that can be dissolved in water to provide metal ions, including transition metal ion salts and oxides of manganese or cobalt; in S2, the iron salt is an iron-containing compound that can be dissolved in water to provide divalent or trivalent iron ions, including ferric chloride, ferric sulfate, ferric nitrate, and ferric acetate; in S3, the conductive substrate is a metal electrode substrate material or a non-metallic electrode substrate material, including gold, silver, nickel, iron, and copper metal electrode substrate materials or conductive glass, carbon cloth, and glassy carbon non-metallic electrode substrate materials.

9. A transition metal-based compound oxygen catalytic material prepared by the modification method according to any one of claims 1 to 8.

10. Use of the transition metal-based compound oxygen catalytic material according to claim 9 in an electrochemical oxygen catalytic functional device, characterized in that: The electrochemical oxygen catalytic functional device is specifically an electrochemical energy conversion and storage device involving oxygen evolution reaction or oxygen reduction reaction, including zinc, iron, lithium, and aluminum metal air batteries.

Citation Information

Patent Citations

  • Preparation of nickel-iron alloy / nitrogen-doped carbon electrocatalyst and application of nickel-iron alloy / nitrogen-doped carbon electrocatalyst in rechargeable zinc-air battery

    CN110071299A

  • Electrodeposition of cobalt or copper alloys and their use in microelectronics

    CN113383115B

  • Electroplating process for preparing permanent magnet FePt thick film through step-by-step electro-deposition

    CN116971000A

  • Low surface energy electrode and manufacturing process thereof

    CN118600507A